Metal removal and recovery using bioelectrochemical technology: The major determinants and opportunities for synchronic wastewater treatment and energy production. (15th September 2020) - Kaushik, A.; Singh, Aradhana
Abstract: Microbial fuel cell (MFC) technology has emerged as a new and attractive bioelectrochemical approach in the last one and a half decade that offers an alternative to conventional treatment methods to remove and recover heavy metals and organics from wastewaters with simultaneous energy production. This technique has advantage over the conventional wastewater treatment techniques, which are energy intensive, sludge producing and with little effectivity at high concentrations. Significant work has been done in the recent years on MFC principle, electrode configuration, biofilm composition, application of MFC in wastewater treatment, metal removal or recovery and energy production. Basically, metal in the cathode chamber acts as acceptor of the electrons released from the oxidation of organic matter in the anode chamber by electrogenic microbes. Literature shows that efficacy of MFCs in removal and recovery of metals and power production is significantly influenced by redox potential of the metal, initial concentration, mix metal systems, carbon source in substrate, pH, biocathode, biofilm composition, gaseous environment in cathode, electrode modification and external resistance, which have been critically reviewed for the first time in the present paper to understand the role of the determinant factors that may be explored for improvement of the MFC performance. The paper provides further insights into the techno-economic aspects of MFC technology and suggests research needs for enhanced performance and reduced costs to increase its feasibility for application at commercial level. Graphical abstract: Image 1 Highlights: Removal and recovery of metals from wastewater in MFC cathode is a new approach. Co-removal of COD from wastewater in anode and electricity production add merit. Manipulating determinant parameters (pH, O2 /N2, C, load ext) improve the process. For metals with low redox potential, use of biocathode is an effective alternative. Techno-economic analysis suggests more research work needed to benefit metal recovery.